PENGOLAHAN AIR LIMBAH MENGGUNAKAN BIOREAKTOR MEMBRAN (BRM) - ASTITI ADITIA (JURNAL ILMIAH MAKSITEK, 2020)
Knowing the origin of wastewater is the basic foundation for designing a waste treatment unit and selecting an effectivetechnology for treating waste. The composition of the wastewater flow will fluctuate depending on the waste water containedin it. When untreated wastewater accumulates and discharged directly into the environment, the decomposition process oforganic matter contained in wastewater will lead to conditions that can disrupt the life of living things around the wastewaterdisposal site, for example, foul smelling gas occurs. In general, wastewater treatment is carried out in four stages,preliminary treatment, primary treatment, secondary treatment, and tertiary treatment. Secondary treatment is also calledbiological treatment because it involves the role of several microbes in the waste or the addition of some microbes to thesystem. Activated sludge system is generally used in the wastewatwer treatment, but there are several disadvantages, oneof the major problems is the quality of the effluent. Therefore, it is necessary to combine the activated sludge system with amembrane bioreactor which can produce good quality effluent, and it can be operated at high MLSS concentrations, so it cantreat a larger volume of wastewater.